Can Kratom (Mitragyna speciosa) Alleviate COVID-19 Pain? A Case Study - Metastasio, Antonio; Prevete, Elisabeth; Singh, Darshan; Grundmann, Oliver; Prozialeck, Walter C.; Veltri, Charles; Bersani, Giuseppe; Corazza, Ornella (Frontiers in Psychiatry, 2020)
among the symptoms of COVID-19 fever, general malaise, pain and aches, myalgia, fatigue and headache can affect the quality of life of patients, even after the end of the acute phase of the infection and can be long lasting. The current treatment of these symptoms, also because COVID-19 patients have been asked not to use nonsteroidal anti-inflammatory drugs (NSAIDs), in particular ibuprofen are often unsatisfactory. Among the above mentioned symptoms malaise and fatigue seem the most difficult to treat. In this case report we describe the use of kratom (Mitragyna speciosa) by a patient with confirmed COVID-19 infection. What we observed was a fast and sustained relieve of the above mentioned symptoms.